Theoretical Insight into the Spectral Characteristics of Fe(II)-Based Complexes for Dye-Sensitized Solar Cells—Part I: Polypyridyl Ancillary Ligands - Xiaoqing Lu; Shuxian Wei; Chi-Man Lawrence Wu; Ning Ding; Shaoren Li; Lianming Zhao; Wenyue Guo (International Journal of Photoenergy)
The design of light-absorbent dyes with cheaper, safer, and more sustainable materials is one of the key issues for the future development of dye-sensitized solar cells (DSSCs). We report herein a theoretical investigation on a series of polypyridyl Fe(II)-based complexes of FeL2(SCN)2, [FeL3]2+, [FeL′(SCN)3]-, [FeL′2]2+, and FeL′′(SCN)2 (L = 2,2′-bipyridyl-4,4′-dicarboxylic acid, L′ = 2,2′,2″-terpyridyl-4,4′,4″-tricarboxylic acid, L″ = 4,4‴-dimethyl-2,2′ : 6′,2″ :6″,2‴-quaterpyridyl-4′,4″-biscarboxylic acid) by density functional theory (DFT) and time-dependent DFT (TD-DFT). Molecular geometries, electronic structures, and optical absorption spectra are predicted in both the gas phase and methyl cyanide (MeCN) solution. Our results show that polypyridyl Fe(II)-based complexes display multitransition characters of Fe → polypyridine metal-to-ligand charge transfer and ligand-to-ligand charge transfer in the range of 350–800 nm. Structural optimizations by choosing different polypyridyl ancillary ligands lead to alterations of the molecular orbital energies, oscillator strength, and spectral response range. Compared with Ru(II) sensitizers, Fe(II)-based complexes show similar characteristics and improving trend of optical absorption spectra along with the introduction of different polypyridyl ancillary ligands.